2016
DOI: 10.1007/s00284-016-0996-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Related to Biofilm Formation in Acinetobacter baumannii and Klebsiella pneumoniae Clinical Strains from Different Pulsotypes

Abstract: The emergence of Acinetobacter baumannii and Klebsiella pneumoniae strains in the hospital environment has been associated with the presence of multiple genetic elements, virulence factors and the ability to form biofilms. This study evaluated the biofilm formation ability of clinical and environmental A. baumannii and K. pneumoniae strains, isolated from various sources and presenting different molecular characteristics, resistance profiles and pulsed-field gel electrophoresis patterns. Fifty-three isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
2
18
1
2
Order By: Relevance
“…Most interesting and intriguing was to find that nonendemic clones produced strong biofilms independent of ESBL production. In agreement with our results are the recent observations by de Campos et al, [ 11 ] who did not find a link between antimicrobial resistance and biofilm production in clinical isolates of K. pneumoniae and A. baumannii . However, our results contrast with other previous studies in which a direct relationship between the antimicrobial resistance and biofilm production has been shown [ 23 25 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Most interesting and intriguing was to find that nonendemic clones produced strong biofilms independent of ESBL production. In agreement with our results are the recent observations by de Campos et al, [ 11 ] who did not find a link between antimicrobial resistance and biofilm production in clinical isolates of K. pneumoniae and A. baumannii . However, our results contrast with other previous studies in which a direct relationship between the antimicrobial resistance and biofilm production has been shown [ 23 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…While it appears that antibiotic resistance coupled to biofilm formation and extracellular fibrillar adhesive appendages have contributed to the global spread of K. pneumoniae and other gram-negative bacilli, the relationship among these factors has not been elucidated [ 11 ]. Recently, the relationship between virulence, multidrug resistance, and biofilm formation in clinical strains of Acinetobacter baumannii and K. pneumoniae was evaluated [ 11 ]. It was found that the ability to form biofilms was not associated with clonal types or multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Environmental isolates collected from patients’ rooms at Federal University of Uberlandia Hospital in Brazil were also reported to produce biofilm. 22 These may suggest that the source of microbial cells may have a great impact on the capacity of the cells to produce biofilm.…”
Section: Ecology and Its Influence On The Formation Of Biofilms By mentioning
confidence: 99%
“…Recently, several studies report the association of antibiotic resistance with biofilm formation in clinical isolates of Klebsiella spp. [11][12][13][14]. Moreover, the role of fimbriae in adhesion and biofilm formation by Klebsiella is also well documented [15,16].…”
Section: Introductionmentioning
confidence: 96%